(untitled) (Journal of Hama University, 2022)
Abstract: Introduction: Fovea palatinae are useful as an indicator of posterior denture border. The relationship between the location of Fovea palatinae to the vibration line has differences and is associated with the types of soft palate. This study was conducted at the Faculty of Dentistry at Al-Andalus University for Medical Sciences, Tartous, Syria. Aim: The aim of this study is to investigate the relationship between clinically determined posterior vibrating line and fovea palatinae and also compare the variations among the different types of soft palate. Materials and Methods: In 120 edentulous patients (73,3% male, %26,7 famale), fovea palatine and posterior vibrating line were marked, and the distance between them was recorded using a metal caliper. The comparisons were made in palatal types and gender as independent variables. Results: Our study results shows in 9,66% subjects vibrating line lies anterior to fovea palatinae, 13,07% subjects it lies at and 77,26% subjects lies behind the fovea palatinae. Statistical analysis showed no significant between gender, soft palate types on location of vibrating line in relation to the fovea palatinae while statistically significant differences were found at the level of (P=0.01) for the location of the vibration line in relation to the palatine fossa. Conclusions: The fovea palatinae was located more posteriorly in the Syrian population and can be used cautiously for locating the posterior extent of maxillary denture. The mean distance of posterior vibrating line from the fovea was found to be 2,55 mm posteriorly. Keywords: Fovea Palatinae, maxillary denture, vibrating line.